2015
DOI: 10.1080/13658816.2015.1111377
|View full text |Cite
|
Sign up to set email alerts
|

Spatial scale and small area population statistics for England and Wales

Abstract: It is well-known that the results of analyses of aggregate data, such as those provided as outputs from censuses, are dependent on the size and shape of the zones used to report the data. However, many users of aggregate census data do not consider how far the zones utilised in their analyses capture spatial information about the population sub-groups they are studying. In addition, future data collection strategies should account for such issues. This article takes as its focus England and Wales, and it seeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…The North-South gap is not surprising, as there is a significant history of socio-economic and health disparities between Northern and Southern England [ 33 , 34 ]. The higher rates of unemployment and no qualifications in the North than in the South are in line with previous research in England [ 35 ]. We also found that alcohol misuse was high in areas with a high prevalence of HL, such as the South West, which over time developed one of the highest prevalence rates of alcohol misuse despite its higher socio-economic status compared to other GORs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The North-South gap is not surprising, as there is a significant history of socio-economic and health disparities between Northern and Southern England [ 33 , 34 ]. The higher rates of unemployment and no qualifications in the North than in the South are in line with previous research in England [ 35 ]. We also found that alcohol misuse was high in areas with a high prevalence of HL, such as the South West, which over time developed one of the highest prevalence rates of alcohol misuse despite its higher socio-economic status compared to other GORs.…”
Section: Discussionsupporting
confidence: 91%
“…Future research should build on this analysis using small area statistics (such as Lower Layer Super Output Areas) and investigate more localised patterns and determinants of place-to-place HL differences in England [ 35 ]. Such research would help to quantify potential ‘area effects’ on hearing health outcomes, allowing for generalisable results of spatial associations with HL rates.…”
Section: Discussionmentioning
confidence: 99%
“…The problem is that these levels are usually somewhat arbitrary; in fact, any one level is usually a mixture of scales because the areal units that comprise it vary in shape and size. There is potential in adopting a more consistent geography such as using the gridded data available at https://popchange.liverpool.ac.uk/ (Lloyd ).…”
Section: Resultsmentioning
confidence: 99%
“…Few population studies employ composition ratio data of the population. As far as the authors of this paper know, the studies by Christopher D. Lloyd [6][7][8][9] are the only ones that focus on the spatial concentration of the population and target the population at the regional or national levels in the United Kingdom. This study considered the characteristics of population composition ratio data to compare the population structure at global and international levels.…”
Section: Methodsmentioning
confidence: 99%